Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0ra05276k
|View full text |Cite
|
Sign up to set email alerts
|

Applications of alkyl orthoesters as valuable substrates in organic transformations, focusing on reaction media

Abstract: In this review we focus on applications of alkyl orthoesters as valuable and efficient substrates to perform various classes of two-component and multi-component organic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 498 publications
(789 reference statements)
0
6
0
Order By: Relevance
“…In view of promoting efficiently the formation of the cyclic amidrazone, the next step of the sequence consists in a cyclisation of the aminohydrazine salt 3 to the cyclic amidrazone 4 a (Scheme 1). At that stage, we turned our attention on reactions from the literature allowing the preparation of cyclic amidine motifs starting from simple diamines in presence of various cyclization reagents including imidoesters, [11] imidazolines, [12] thioamides, [13] orthoesters, [14] carboxylic acids, [15] aldehydes in situ combined with oxidants, [16] as well as catalystor acid-based processes with nitrile or nitroalkanes. [17] Based on these considerations, we first explored the formation of cyclic amidrazones 4 a by screening several cyclization partners (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In view of promoting efficiently the formation of the cyclic amidrazone, the next step of the sequence consists in a cyclisation of the aminohydrazine salt 3 to the cyclic amidrazone 4 a (Scheme 1). At that stage, we turned our attention on reactions from the literature allowing the preparation of cyclic amidine motifs starting from simple diamines in presence of various cyclization reagents including imidoesters, [11] imidazolines, [12] thioamides, [13] orthoesters, [14] carboxylic acids, [15] aldehydes in situ combined with oxidants, [16] as well as catalystor acid-based processes with nitrile or nitroalkanes. [17] Based on these considerations, we first explored the formation of cyclic amidrazones 4 a by screening several cyclization partners (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several studies reported the use of triethyl orthoformate to produce cyclized derivatives 64 . The tricyclic pyrrolo[3,2- d ]pyrimidine derivatives 9a–c were achieved by refluxing compounds 5a–c with excess triethyl orthoformate ( Scheme 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, many strategies have been developed for the synthesis of N ‐formyl amines using orthoesters [19–23] . Notably, alkyl orthoesters are useful and efficient starting materials for two‐component and multi‐component organic reactions [24] . They can also be obtained from mixed anhydrides include formic acid‐EDAC, [25] formic acid‐DCC, [26] acetic formic anhydride, [27] and formyl pivaloyl anhydride [28] .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Notably, alkyl orthoesters are useful and efficient starting materials for two-component and multi-component organic reactions. [24] They can also be obtained from mixed anhydrides include formic acid-EDAC, [25] formic acid-DCC, [26] acetic formic anhydride, [27] and formyl pivaloyl anhydride. [28] Formylation with formates consisting of 2,2,2-trifluoroethyl formate, [29] cyanomethyl formate, [30] and pentafluorophenyl formate [31] have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%